The ant genus Myopias Roger, 1861 (Hymenoptera: Formicidae: Ponerinae) in Thailand, with descriptions of three new species - Jaitrong, Weeyawat; Tasen, Wattanachai; Guénard, Benoit (Zootaxa, 2018)
The genus Myopias Roger, 1861 is distributed in the Australian, Oceanian, Oriental and southern Sino-Japanese realms. Currently 40 valid species and three subspecies have been described, but none have ever been recorded for Thailand. Here we review the species of Thailand, recognizing seven in total. Four are new records of previously described species: Myopias bidens (Emery, 1900), M. crawleyi (Donisthorpe, 1941), M. maligna punctigera (Emery, 1900), and M. mandibularis (Crawley, 1924). Three new species are described: Myopias minima sp. nov. from southern Thailand, M. sakaeratensis sp. nov. from eastern Thailand and M. sonthichaiae sp. nov. from northern and western Thailand. The queen caste of M. mandibularis is described here for the first time and additional descriptions of other species are provided. All these species were found to nest in rotten wood on the forest floor.